Clinical implications of gene polymorphisms in venous leg ulcer: A model in tissue injury and reparative process - Zamboni, Paolo; Gemmati, Donato (Thrombosis and Haemostasis, 2007)
Wound healing is a multi-step process involving complex pathways at cell and molecular level. Lack of understanding of the molecular mechanisms and pathogenesis of impaired healing in chronic leg ulcers limits clinical assessment and management. In addition, individual genetic background certainly affects the response to treatment and specifically modulates the unfavourable lesion environment.Although the number of actors involved in the aetiology of chronic wounds is extremely high, the ability to find out groups of candidate genes on the basis of clinical and physio-pathological findings is a crucial step.The present review demonstrates how recognition of functional gene variants, mostly single nucleotide polymorphisms (SNPs), significantly involved in wound healing and venous ulcer establishment, extra- ordinarily helps prognosis, diagnosis and treatment of chronic wounds.We deal with on how one can manage SNPs in coagulation factor XIII (FXIII) and hemochromatosis (HFE) genes as molecular markers or prognostic tools. In this fashion, we could pave the way for strategies aimed to single out in advance categories of patients at increased risk to develop severe complications of chronic venous disorders, or to predict the healing time after surgical intervention. Because of its relevant epidemiology and its easily visualized lesions, venous leg ulcer is an ideal model for investigating, the mechanisms of tissue injury and reparative process,as well as the influence of different genetic backgrounds.
Keywords: Wound healing; single nucleotide polymorphisms; oxidative; stress; inflammation; factor XIII; iron